Increased prevalence of idiopathic scoliosis in patients treated for childhood haematopoietic malignancy. (1st August 2021) - Sim, Francis C. J.; Birley, Emma; Khan, Almas L.; Loughenbury, Peter R.; Millner, Peter
Abstract : Aims: The aim of this study was to determine whether there is an increased prevalence of scoliosis in patients who have suffered from a haematopoietic malignancy in childhood. Methods: Patients with a history of lymphoma or leukaemia with a current age between 12 and 25 years were identified from the regional paediatric oncology database. The medical records and radiological findings were reviewed, and any spinal deformity identified. The treatment of the malignancy and the spinal deformity, if any, was noted. Results: From a cohort of 346 patients, 19 (5.5%) had radiological evidence of scoliosis, defined as a Cobb angle of > 10°. A total of five patients (1.4% of the total cohort) had a Cobb angle of > 40°, all of whom had corrective surgery. No patient with scoliosis had other pathology as a possible cause of the scoliosis and all had been treated with high doses of steroids for leukaemia, either acute or chronic myeloid, or acute lymphoblastic. Conclusion: There is an increased prevalence of idiopathic-like scoliosis and larger curves (Cobb angle of > 40°) associated with childhood leukaemia, which has not been previously reported in the literature. Causative factors may relate to the underlying disease process and/or its treatment. Cite this article: Bone Joint J  2021;103-B(8):1400–1404.